The Effect of ESG Disclosure and R&D Intensity on Financial Performance: The Moderating Role of Board Gender Diversity - Prihatiningtias, Yeney Widya; Saraswati , Ni Made Ananda (International Journal of Social Science and Business, 2025)
Despite its economic contribution, Indonesia’s manufacturing sector struggles with sustainability, innovation, and gender diversity, and the impact of these factors on financial performance remains unclear. This study examined the effects of environmental, social, and governance disclosure and research and development intensity on the financial performance of manufacturing companies in Indonesia, and assessed whether gender diversity on the board of directors moderated these relationships. Data from 162 manufacturing firms listed on the Indonesia Stock Exchange during 2021–2023 were analyzed using multiple regression and moderated regression analysis. The results showed that environmental and social disclosures positively influenced return on assets and return on equity, while governance disclosure positively affected Tobin’s Q. Research and development intensity had a positive effect on all financial performance indicators. Gender diversity on the board strengthened the positive effects of social and governance disclosures on return on assets and Tobin’s Q, and also enhanced the impact of research and development intensity on Tobin’s Q. These findings indicated that transparent sustainability reporting and innovation investment improved both accounting-based and market-based performance, and that diverse boards amplified certain strategic impacts. The study concluded that integrating sustainability practices and innovation with gender-diverse leadership contributed to better financial outcomes, offering practical implications for managers, investors, and policymakers seeking to enhance governance and long-term corporate value.